Wanita Usia 39 Tahun dengan Ensefalopati Hipertensi: Laporan Kasus - Neema Putri Prameswari; Vioren; Anisa Ramadhanti; Zam Zanariah Ibrahim (Puslitbang Sinergis Asa Professional, 2022)
Hypertensive encephalopathy is an acute reversible syndrome caused by a sudden increase of blood pressure so crosses the limits of brain auto-regulation. The objective of writing this scientific paper was to present clinical manifestations of hypertensive encephalopathy and report the favorable clinical outcomes in hypertensive encephalopathy patients with comprehensive therapy. This paper is an empirical case study investigates the symptoms of Hypertensive Encephalopathy in real life. Female, 39 years old complaints of sudden seizures, before the seizure she felt of non-throbbing headache all over her head. There was an increase in blood pressure of 200/130 mmHg. On neurologic-ophthalmologic examination, her right eye had no light perception (NLP), while on other neurological functions there were no abnormalities. She was hospitalized and treated with antihypertensive drugs, that are Amlodipine and Lamipril, during inpatient the DASH diet was given. The patient showed improvement, then was discharged on the 5th day of treatment. Diagnosis of hypertensive encephalopathy was made in this patient built upon high blood pressure plus neurologic symptoms and the exclusion of other conditions that could cause similar symptoms. Antihypertensives were used carefully at a target blood pressure of 150/100 mmHg (20% of MAP). Application of DASH diet has an effect for lowering blood pressure due to the restriction of sodium intake from food. Management of hypertensive encephalopathy includes lowering blood pressure but it’s not recommended aggressively because it can cause ischemia. Preventive measures are very important, research is needed on predictive factors for hypertension encephalopathy and a high level of alertness in risk groups.